Thyrotropin exacerbates insulin resistance by triggering macrophage inflammation in subclinical hypothyroidism - Haihong Zhang; Zekun Zeng; Yan Liu; Wenfang Zheng; Jianling Wang; Yao Yao; Yanan Wang; Meiju Ji; Peng Hou (Experimental and Molecular Medicine)
Abstract In subclinical hypothyroidism, the levels of serum thyroid-stimulating hormone (TSH) are positively correlated with insulin resistance; however, the precise mechanism is unclear. Except for thyroid follicular epithelial cells, macrophages express the highest levels of TSHR. Thus, we speculate that TSH may promote insulin resistance by triggering macrophage inflammation. Here we established a mouse model of TSH receptor (Tshr) myeloid-specific knockout (Tshr MKO ) and found that Tshr MKO mice showed improvement on high-fat diet-induced obesity and insulin resistance compared with wild-type mice (Tshr f/f ). In addition, Tshr MKO mice exhibited decreased infiltration and M1 polarization of macrophages in liver, adipose and skeletal muscle. Co-culture experiments proved that Tshr-deficient macrophages decreased gluconeogenesis in hepatocytes but increased glucose uptake in adipocytes and skeletal muscle cells by improving the insulin signaling pathway. Mechanistically, increased TSH levels in subclinical hypothyroidism promoted the secretion of cytokines IL-1α, IL-1β and IL-6 by inducing macrophage M1 polarization, which upregulated EGR1 to transcriptionally activate LCN2 and SOCS3 in insulin target cells, thereby exacerbating insulin resistance. These effects could be reversed by IL-1 and IL-6 blockers IL-1RA and IL-6ST. Thus, we provided mechanistic insights into the predisposition to insulin resistance in subclinical hypothyroidism and revealed the role of TSH in metabolic disorders.